ANALYSIS OF FINANCIAL HEALTH LEVEL OF PT. GARUDA INDONESIA BASED ON FINANCIAL ASPECT OF KEPUTUSAN MENTERI BADAN USAHA MILIK NEGARA NOMOR: KEP-100/MBU/2002 - Banne, Vivaldi R.; Kalangi, Josep B.; Wangke, Shinta J.C. (Universitas Sam Ratulangi, 2019)
Abstract: Aviation industry is one of the largest commercial industry in Indonesia. There are several of aviation companies out there, one of them is Garuda Indonesia. Garuda Indonesia is one of the largest aviation company in Indonesia. It is also an SOE which means they are one of the income sources of Indonesia and is overseen by the minister of SOE Rini Sumarno. Each of the SOE can be monitored and measured by using the Keputusan Menteri Badan Usaha Milik Negara Nomor : Kep-100/Mbu/2002 to determine whether its considered a healthy company or not. This study uses quantitative method with ratio analysis. Multiple ratios are going to be analyzed based on whats written in the Keputusan Menteri Badan Usaha Milik Negara Nomor : Kep-100/Mbu/2002. Finding of this research shows that there are few ratios that Garuda scored high and there are some that Garuda scored low, notably ROE, current ratio and cash ratio. From the results, it is recommended for Garuda Indonesia to increase their profit margin and processing or even get rid of their unused assets.Keywords: financial performance of garuda indonesia, financial ratio analysis, keputusan menteri badan usaha milik negara nomor : kep-100/mbu/2002